Label-Free Proteomics Assisted by Affinity Enrichment for Elucidating the Chemical Reactivity of the Liver Mitochondrial Proteome toward Adduction by the Lipid Electrophile 4-hydroxy-2-nonenal (HNE) - Tzeng, Shin-Cheng; Maier, Claudia S. (Frontiers in Chemistry, 2016)
The analysis of oxidative stress-induced post-translational modifications remains challenging due to the chemical diversity of these modifications, the possibility of the presence of positional isomers and the low stoichiometry of the modified proteins present in a cell or tissue proteome. Alcoholic liver disease (ALD) is a multifactorial disease in which mitochondrial dysfunction and oxidative stress have been identified as being critically involved in the progression of the disease from steatosis to cirrhosis. Ethanol metabolism leads to increased levels of reactive oxygen species (ROS), glutathione depletion and lipid peroxidation. Posttranslational modification of proteins by electrophilic products of lipid peroxidation has been associated with governing redox-associated signaling mechanisms, but also as contributing to protein dysfunction leading to organelle and liver injury. In particular the prototypical α,β-unsaturated aldehyde, 4-hydroxy-2-nonenal (HNE), has been extensively studied as marker of increased oxidative stress in hepatocytes. In this study, we combined a LC-MS label-free quantification method and affinity enrichment to assess the dose-dependent insult by HNE on the proteome of rat liver mitochondria. We used a carbonyl-selective probe, the ARP probe, to label HNE-protein adducts and to perform affinity capture at the protein level. Using LC-MS to obtain protein abundance estimates, a list of protein targets was obtained with increasing concentration of HNE used in the exposure studies. In parallel, we performed affinity capture at the peptide level to acquire site-specific information. Examining the concentration-dependence of the protein modifications, we observed distinct reactivity profiles for HNE-protein adduction. Pathway analysis indicated that proteins associated with metabolic processes, including amino acid, fatty acid and glyoxylate and dicarboxylate metabolism, bile acid synthesis and TCA cycle, showed enhanced reactivity to HNE adduction. Whereas, proteins associated with oxidative phosphorylation displayed retardation toward HNE adduction. We provide a list of 31 protein targets with a total of 61 modification sites that may guide future targeted LC-MS assays to monitor disease progression and/or intervention in preclinical models of ALD and possibly other liver diseases with oxidative stress component.